Substitution of microalgae by bioflocs as a food source for the brine shrimp Artemia franciscana. (11th June 2022) - Hasan‐Nataj‐Niazi, Elaheh; Agh, Naser; Noori, Farzaneh; Atashbar, Behrooz; Van Stappen, Gilbert
Abstract: This research was done to investigate the application of halophilic bacteria in a biofloc production system to grow Artemia franciscana in the laboratory, in which part of a standard microalgae feeding regime was replaced by bioflocs. Bioflocs were produced according to a standard procedure, using rice bran and vinasse as carbon sources, a commercial probiotic product, and halophilic Bacillus sp., originating from Urmia Lake, Iran, as halophilic bacteria. Three successive laboratory culture tests were conducted at salinities 60 (experiments 1 and 3) and 120 g L −1 (experiment 2) for 21, 14 and 14 days, respectively. Five feeding regimes were examined; the control treatment feeding a standard regime of only the microalga Dunaliella tertiolecta, and four biofloc treatments: 90% and 75% replacement of microalgae by bioflocs, both without and with halophilic addition. Depending on the experiment, Artemia performance was assessed as growth, reproductive performance, fatty acid and proximate composition and/or digestive enzyme activity. Applying halophilic bacteria in biofloc systems had no significant effect on the measured parameters. We further conclude that Artemia franciscana can be cultured successfully using bioflocs as the main food source, with limited microalgae supplementation (10%–25%) with no significant effect on survival, length, proximate composition and levels of most fatty acids in Artemia biomass. A number of fecundity parameters were negatively affected by 75% substitution of microalgae by bioflocs. This research opens interesting perspectives to produce Artemia at a bigger scale, e.g., in tanks or pond conditions, where production of sufficient quantities of suitable microalgae species might be problematic.